The significance of multidisciplinary classifications based on transbronchial pathology in possible idiopathic interstitial pneumonias. Issue 28 (10th July 2020) - Wang, Weixue; Xu, Jian; Liu, Chunfang; Feng, Ruie; Zhao, Junjun; Gao, Na; Jiang, Ling; Zhang, Xiaolin; Han, Xue; Ren, Lina; Zhao, Xiaohui; Liu, Yuan
Abstract : Abstract: Surgical lung biopsy is regarded as the golden standard for the diagnosis of idiopathic interstitial pneumonias (IIPs). Here, we attempted to show the diagnostic accuracy of multidisciplinary classifications based on transbronchial pathology including transbronchial lung cryobiopsy (TBLC), bronchoalveolar lavage fluid (BALF) and endobronchial ultrasound-guided transbronchial needle aspiration biopsy (EBUS-TBNA). Patients with suspected interstitial lung diseases admitted from June 1, 2016 to December 31, 2018 were involved. Patients with known causes of interstitial lung diseases and typical idiopathic pulmonary fibrosis diagnosed through clinical, radiological information were excluded. Patients with atypical idiopathic pulmonary fibrosis and possible IIPs accepted transbronchial pathological evaluation. Initial multidisciplinary diagnosis (MDD) classifications were made depending on clinical, radiological and transbronchial pathological information by a multidisciplinary team (MDT). The final MDD classifications were confirmed by subsequent therapeutic effects. All patients were followed up for at least 6 months. A total of 70 patients were finally involved. The samples of lung parenchyma extracted through TBLC were enough for confirmation of pathological diagnoses in 68.6% (48/70) cases. Samples of 6 cases were extracted by EBUS-TBNA. Bacteriological diagnoses were positive in 1 case by BALF. Pathological diagnoses of 77.1% (54/70) cases were achieved through TBLC, EBUS-TBNA and BALF. During the follow up study, the pulmonary lesions of 60% patients were improved, 11.43% were relapsed when glucocorticoid was reduced to small dose or withdrawal, 14.29% were leveled off and 8.57% were progressed. The diagnoses of 4 patients with progressed clinical feature were revised. As a result, 94.3% initial MDD classifications based on transbronchial pathology were consistent with the final MDD, and the difference of diagnostic yield wasn't significant between initial and final MDD ( Z  = −1.414, P  = .157). Classifications of IIPs based on transbronchial pathology were useful and quite agreed with final MDD.